2021
DOI: 10.1007/s00192-020-04638-1
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for pelvic organ prolapse: systematic review

Abstract: Introduction and hypothesis We aimed to summarize the knowledge on the pathogenesis of pelvic organ prolapse (POP) generated in animal models. Methods We searched MEDLINE, Embase, Cochrane and the Web of Science to establish what animal models are used in the study of suggested risk factors for the development of POP, including pregnancy, labor, delivery, parity, aging and menopause. Lack of methodologic uniformity precluded meta-analysis; hence, results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…The optimal POP animal models for POP should be squirrel monkeys and ewes [ 58–60 ], which could simulate the pathophysiology of humanity. However, abdominal defect models could be used as a POP model to evaluate the repair effects and host responses of implanted materials [ 22 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optimal POP animal models for POP should be squirrel monkeys and ewes [ 58–60 ], which could simulate the pathophysiology of humanity. However, abdominal defect models could be used as a POP model to evaluate the repair effects and host responses of implanted materials [ 22 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anatomical, biomechanical, biochemical, and histological studies in nulliparous, primiparous, and multiparous ewes demonstrated similar rates of POP after vaginal delivery to that observed in humans, due to a large foetal head to body ratio and relatively comparable pelvic anatomy [ 88 , 89 ]. The diameter and length of the ovine and human vagina are relatively similar, and the ovine pelvic architecture relies on three levels of support, similar to the DeLancey model described in humans [ 90 , 91 ]. Both ovine and human vaginal wall consist of four histological zones of epithelium, lamina propria, muscularis, and adventitia [ 92 ].…”
Section: Engineering Novel Meshes With Emscmentioning
confidence: 99%
“…A recent systematic review of the literature showed that several animal models have been used in the study of the pathophysiology of POP, such as lagomorphs, rodents, sheep, and NHPs. 50 The authors concluded that in several species there are measurable effects of pregnancy, delivery, and iatrogenic menopause, but there is not a single uniform pattern. However, only squirrel monkeys develop clinical POP spontaneously.…”
Section: Popmentioning
confidence: 99%